Data modelling for GIS based saturation excess overland flow - Mohamad Yusoff, Izham; Abdul Rahman, Alias; Katimon, Ayob; Ismail, Wan Ruslan (2008)
In a Geographic Information System (GIS), the transformation of geographical data (e.g. actual locations and physical characteristics of objects on the Earth surface) into geographic information dealt with complex series of process and procedures. In hydrologic modelling, streamflow is one of the main physical geographic apprearance within nature of hydrologic cycle. Rapid population growth,constructions, urbanization, and industrialization have increased impervious area causing hazardous impact towards rate of stormwater infiltrated into soil. Thus the overland flow in a post-development area becomes greater than the pre-development area. Within GIS, all stream networks, surface structures and its properties must be assigned and preserved with coordinate systems and map projections respectively known as georeferencing. Hence, any GIS based hydrologic applications need careful understanding in terms of map projections, coordinate systems and its transformations, scales and grid resolutions while entering spatial data. At present, there is still no unifying evidence available that provides a coherent and satisfactory explaination for the integration of the core GIS based saturation excess mechanisms into the streamflow generating process. Concepts of georeferencing need to be applied while performing GIS based saturation mechanism and to sustain the existing spatial properties of soil and land use. This study aims to visualize the effects of georeferencing system towards determine areas and total overland flow volume generated from Saturation Excess Overland Flow (SEOF) process using topographic wetness index (TWI) and antecedent soil-moisture conditions (AMC). Both factors are analysed by focusing on spatial object preservation techniques of conformal based Rectified Skew Orthomophic (RSO) and equidistance based Cassini-Soldner projections. This study is carried out at Sungai Pinang basin, located in North East coast of Penang Island, Malaysia. The areas and discharge from SEOF areas are determined and compared based on the map scale of 1 : 25 000. Digital layers of Sungai Pinang basin are constructed using Autodesk Map 2004 software, while Digital Elevation Models (DEM) construction and SEOF are determined using Spatial Analyst extension within ArcView GIS software. Local authorities could find the results are useful to evaluate the effectiveness of flood management control, sustainability for long-term development purposes, stream restoration, rehabilitation and relocation of construction projects.